Flow Rate and Raspberry Pi-Based Paper Microfluidic Blood Coagulation Assay Device - Sweeney, Robin E.; Nguyen, Vina; Alouidor, Benjamin; Budiman, Elizabeth; Wong, Raymond K.; Yoon, Jeong-Yeol (IEEE sensors journal, 2019)
Monitoring blood coagulation in response to an anticoagulant (heparin) and its reversal agent (protamine) is essential during and after surgery, especially with cardiopulmonary bypass. A current clinical standard is the use of activated clotting time, where the mechanical movement of a plunger through a whole blood-filled channel is monitored to evaluate the endpoint time of coagulation. As a rapid, simple, low-volume, and cost-effective alternative, we have developed a paper microfluidic assay and Raspberry Pi-based device with the aim of quantifying the extent of blood coagulation in response to varying doses of heparin and protamine. The flow rate of blood through the paper microfluidic channel is automatically monitored using the Python-coded edge detection algorithm. For each set of the assay, 8-μL of fresh human whole blood (untreated and undiluted) from human subjects is loaded onto each of eight sample pads, which have been preloaded with varying amounts of heparin or protamine. The total assay time is 3-5 min including the time for sample loading and incubation.